MODEL PENGEMBANGAN BUDAYA PATEN DI KATANGAN KAIIfIPUS DALAM RANGKA MENIJMBUHKEN4BAruGKAN IN DIGENOIJS TECH NOTOGICAL CAPABELITIffiS - idris id (Jurnal ADIL, 2015)
Ihts research is nainly focused an sacialization af ir';i*,ilscii.;aipraperty rights law, particularly lssues on indusiry-basoc ,caieni, il lsfurlher expeeted ia prompt legal awareness of !il* no*rl ferintellectual rights law to secure produefs and thek processlngteohnologies, Specificatly, lho objectives of fnis rssearr;h ar* (ai icidentify and to analyse the need for patent culture develapment aswell as to promote awareness of the need far intellectual rignts lawand (b) to create a model of patent culture and patent au?arenessthraugh sucfi measures as socialization, direct sen'rce, andincentive, Ihis research, canducted wiih normative and empirtcmethod, manages to conciude (a) that, to nufture indigenoustechnological capabilities, the need af academics as prospecflveinventors for patent culture develapment includes*atfiv{tQ athers*legal protection, partnership, training, and crganization, and (b) thatthe suitable model of patent culture development is through activecounselling on intellectual rights and by providing incentives (fromthe government) when the locals prccess patent certificates andseek legal protection in running their business, E/rglble inventionsmust meet patent requirements: novelty, invenflve sfeps, anCindustrial applicability. Ihose in need far patent licenses maycontact fhe assrgned consultants,Keywords z Patent culture, indigenous technological capabiliiy